Distinct Vulnerability and Resilience of Human Neuroprogenitor Subtypes in Cerebral Organoid Model of Prenatal Hypoxic Injury - Daviaud, Nicolas; Chevalier, Clément; Friedel, Roland H.; Zou, Hongyan (Frontiers in Cellular Neuroscience, 2019)
Prenatal hypoxic injury (HI) is a leading cause of neurological disability. The immediate and long-term effects of hypoxia on progenitor homeostasis and developmental progression during early human brain development remain unclear. This gap is due to difficulty to access human fetal brain tissues and inadequate animal models to study human corticogenesis. Recent optimizations of cerebral organoid models derived from human embryonic stem (ES) cells present new opportunities to investigate pathophysiology of prenatal HI. Here, we implemented a transient HI model using human cerebral organoids with dorsal forebrain specification. We demonstrated that transient hypoxia resulted in immediate and prolonged apoptosis in cerebral organoids, with outer radial glia (oRG), a progenitor population more prominent in primates, and differentiating neuroblasts/immature neurons suffering larger losses. In contrast, neural stem cells in ventricular zone displayed relative resilience to HI and exhibited a shift of cleavage plane angle favoring symmetric division, thereby providing a mechanism to replenish the stem cell pool. Furthermore, we defined the vulnerable window and neurodifferentiation stages that are particularly sensitive to HI. Understanding cell type-specific and stage-dependent effects of prenatal HI on survival and mitotic behavior of human neuroprogenitor subtypes during early human corticogenesis helps elucidate the etiology of neurodevelopmental disorders, and provides a therapeutic starting point to protect the vulnerable populations at critical timeframes.